Implementasi Metode Pembelajaran Eksploratif dalam Mengintegrasikan Nilai-Nilai Eko-Teologi pada Mata Pelajaran Pendidikan Agama Islam di Sekolah SMP Terpadu YPP Jamanis Desa Karangbenda, Kecamatan Parigi, Kabupaten Pangandaran: Pengabdian - Rubai Misbahul Alam, Dede; Rizki Gunawan Hasibuan, Akmal; Muslim Taman, M.; Bujava, Aditya; Nazriyah; Mutaqin, Jaenal; Zen, Puad; Arya Yanuar, Fitra; Saidah; Naufal Zidni, Moh; Kurnianto, Doni (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community engagement activity aims to describe the implementation of an exploratory learning method in integrating eco-theological values into Islamic Religious Education (PAI) at SMP Terpadu YPP Jamanis, Pangandaran. The study focuses on lesson planning, exploratory strategies, in- and out-of-class activities, and student involvement in connecting Islamic teachings with environmental issues. Using a qualitative case study approach, data were collected through interviews, participant observation, and documentation. Findings show that teachers designed contextual learning using the surrounding environment as a learning medium, applying strategies such as field observation, case studies, reflective discussions, and mini projects. PAI materials were developed thematically, linking environmental issues with Quranic verses through a contextual hermeneutic approach. Learning activities were dynamic, involving both visual media in the classroom and direct observation outside. Students actively participated and began applying eco-theological values in daily life. This learning model effectively fosters religious awareness and sustainable environmental responsibility.